Analysis of Claviceps africana and C. sorghi from India using AFLPs, EF1 gene intron 4, and betatubulin gene intron 3 - Tooley, P.; Carras, M.; Pazoutova, S.; Bandyopadhyay, Ranajit (Elsevier, 2006)
Isolates of Claviceps causing ergot on sorghum in India were analysed by AFLP analysis, and by analysis of DNA sequences of the EF-1α gene intron 4 and β-tubulin gene intron 3 region. Of 89 isolates assayed from six states in India, four were determined to be C. sorghi, and the rest C. africana. A relatively low level of genetic diversity was observed within the Indian C. africana population. No evidence of genetic exchange between C. africana and C. sorghi was observed in either AFLP or DNA sequence analysis. Phylogenetic analysis was conducted using DNA sequences from 14 different Claviceps species. A multigene phylogeny based on the EF-1α gene intron 4, the β-tubulin gene intron 3 region, and rDNA showed that C. sorghi grouped most closely with C. gigantea and C. africana. Although the Claviceps species we analysed were closely related, they colonize hosts that are taxonomically very distinct suggesting that there is no direct coevolution of Claviceps with its hosts.